(untitled) (Research, Society and Development, 2022)
The genus Chromobacterium spp. are gram-negative bacilli, which may or may not have characteristic purple pigmentation, and are mainly isolated from soil, water and infected patients. The main representative species of this genus is C. violaceum, responsible for a high mortality rate among those infected. The aim of this study was to genetically characterize and broadly compare phenotypic characteristics between the genus Chromobacterium species described in the literatureand bacterial isolates. This study is an experimental research, in which sequencing and phenotypic tests of bacterial isolates were carried out for comparison with species of the genus Chromobacterium. Two strains were identified, CRJL01 and CRJL02 that have characteristics of Chromobacterium spp species. These isolates showed high resistance to antibiotics, tolerance and resistance to metals, biochemical and physiological versatility of the CRJL01 and CRJL02 strains. In the sequencing of the 16S rRNA gene, the CRJL01 strain showed similarity with the C. piscinae strain. The CRJL02 strain showed similarity with the C. subtsugae strain. This work is the first report in 40 years of Chromobacterium spp. in the Brazilian Midwest – Goiás, in water samples. This isolated genus has a wide applicability for the pharmaceutical, food and cosmetic industries, due to the production of its purple/violet pigment known as violacein, and its bioprospecting is of great importance. Thus, this study is a kick-off for exploring your produced pigment.